Effect of 6-week combined training on salivary cortisol levels, total Olympic lifting performance and anxiety levels in elite male Olympic weightlifters - Faizan, M.; Ahuja, A.; Ansari, S.; Sharma, S.; Ngomdir, K.; Alam, M. F. (Sport Sciences for Health, 2024)
Background Weightlifting is one of the Olympic sports. Stress and anxiety are highly prevalent in sports and higher stress and anxiety levels seem to affect performance. There are several training methods used to enhance performance. However, there seems to be a scarcity of studies regarding the effect of training on psycho-physiological measures of performance.